Stunting and wasting rates among pre-school age children in Yangon and Ayeyarwady, October–November 2023 - Myanmar Agriculture Policy Support Activity (International Food Policy Research Institute, 2024)
The outbreak of COVID-19 in 2020 and the military takeover of the democratically elected government in early 2021 has largely prevented the implementation of in-person surveys necessary for the collection of anthropometric data. To redress this knowledge gap, we implemented an in-person survey of mothers (caregivers) and young children in urban and peri-urban Yangon and rural Ayeyarwady in October and November 2023. This in-person 11th round of the Rural-Urban Food Security Survey (RUFSS) involved data collection on a wide range of socioeconomic indicators, but also child anthropometric outcomes such as length and weight. In this study, we report results for height-for-age z scores (HAZ) and weight-for-height z scores (WHZ) relative to international reference standards, as well as stunting (HAZ < -2) and wasting (WHZ < -2). Because of high and rising rates of overweight/obesity among adults in the RUFSS survey, we also examined the number of children were overweight (WHZ > +2) and mildly overweight (+1 <WHZ< +2).